ANALISIS FAKTOR PENGHAMBATPENERAPAN KEBIJAKAN SANITARY LANDFILL DI TPA JATIBARANG SEMARANG SESUAI DENGAN UNDANG-UNDANG NO. 18 TAHUN 2008 TENTANG PENGELOLAAN SAMPAH - ELLI YOANA SUSANTI; SUWANTO ADHI; GHULAM DZUNUWANUS (Journal of Politic and Government Studies, 2016)
Population grows significantly changing consumption pattern has increasing amount of waste in community that affect diversity of garbage in Semarang City. In order to diminish the amount of waste and prevent its detrimental effect on environment, the government issued Constitution Number 18 Year 2008 about Waste Management which elaborates mechanism of waste management, namely Sanitary Landfill. Since 1995, Sanitary Landfill has been applied in Jatibarang Landfill, Semarang, but nowadays implementation is not applied optimally as several problems found.The purpose of this research is analyze inhibiting factors of the Sanitary Landfill’s application in Jatibarang Landfill as well as issues in waste management in Semarang City. This research is a descriptive analytic research which uses a qualitative approach. Data collected through interviews with informants, direct observation in the study site, and documentation studies conducted on various documents relevant to this study.The result shows that final processing of waste in the Jatibarang Landfill tend to use the Controlled Landfill system as Sanitary Landfill system cannot function properly. It is influenced by the separation of waste by resources has not worked well, increase in waste generation, budget realization has not be absorbed maximally, and weather factor.Recommendations that can be given are raising public awareness of waste management through government programs, involving the Head of Neighborhood Unit in oversight of waste management, improvement of policy formulation of waste management in landfill, and maximized budget absorption by considering the scale of priority of waste problems.Keywords: Inhibiting Factor, Sanitary Landfill, Waste Management